Eksistensi Partai Demokrasi Indonesia Perjuangan dalam pemilu legislatif di Kabupaten Subang 1999-2014 (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2023)
This study aims to identify political programs, strategies and the impact of the Indonesian Democratic Party of Struggle (PDIP) in Subang Regency. The method used by researcher is historical method with a multidisciplinary approach. PDIP in Subang Regency had programs aimed at commoners or the underprivileged. At the beginning of the development, the PDIP in Subang Regency programs were carriedout by internal party programs. The next period began to develop programs aimed at the fields of economic field, social, and politic. PDIP’s strategies in the victory of legislative elections is mostly carried out in various ways namely staying firm on party ideology, the presence of Bung Karno and Megawati figures as figures who have influence in the party and in its campaign. The cadres Indonesian Democratic Party of Struggle has a close relationship with the community and directly involved with the community in developing the Subang Regency region, selecting and mapping the legislative candidates appropriately in each chosen region. PDIP in Subang Regency succeeded in making its cadres in important positions in the Subang Regency Government as the Regent and Deputy Regent, as well as the chairman of the Subang Regency Assembly at reginal for four periods namely 1999-2014.
Keywords: Indonesian Demokratic; Legislative elections; Party of Struggle; Privatizationdefense; Subang Regency